ENGLISH TEACHING TODAY: WORLDWIDE EXPERIENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the current trends, challenges, and successful practices in English language teaching (ELT) across the globe. Drawing upon experiences from various countries, it highlights innovative methods, teacher trining standards, and the role of technology in enhancing English proficiency. The article emphasizes the importance of cultural adaptation and learner-centered approaches in different educational contexts. By comparing global practices, it provides valuable insights for educators, policymakers, and learners aiming to improve language instruction in diverse environments.